Dielectrophoretic 3D‐focusing for on‐chip flow cytometry. (22nd April 2020) - Krishna, Salini; Alnaimat, Fadi; Hilal‐Alnaqbi, Ali; Khashan, Saud; Mathew, Bobby
Abstract : Model‐based analysis of a dielectrophoretic microfluidic device for realising 3D‐focusing is presented in this work. The electrode configuration is made up of several finite‐sized planar electrodes positioned on either side of the microchannel's top and bottom surfaces; the electrodes on the top surface and bottom surface of the same side form a pair. The forces associated with inertia, buoyancy, gravity, and dielectrophoresis are included in the model. As per the model, it is possible to use the proposed device to achieve 3D‐focusing at the desired location along the width of the microchannel. Also, the proposed device can achieve 3D‐focusing irrespective of the type of micro‐scale entity. Two parameters for quantifying the efficacy of the microfluidic device in achieving 3D‐focusing are presented – horizontal and vertical focusing parameters. The model demonstrates that the radius of micro‐scale entity, electrode/gap lengths, electrode width, microchannel height, number of electrodes, applied electric potentials, and volumetric flow rate influence horizontal and vertical focusing parameters. The mathematical model is thus useful in designing dielectrophoresis‐based 3D‐focusing with desired performance metrics for on‐chip flow cytometry.